Educational intervention instrument for self-care in nutritional health: evaluation in Mayan Mexican communities - Gullian Klanian, Mariel; Sánchez Solís, Maria J.; Cutz de Ocampo, Joel (International Journal Of Community Medicine And Public Health, 2025)
Background: In rural communities, foodborne illnesses pose a significant public health challenge due to limited access to education and health resources, which increases the risk of improper food practices. It is crucial to develop and implement targeted educational interventions tailored to the specific needs and characteristics of these areas to effectively prevent these health issues. This study aimed to design and validate an educational intervention instrument adapted to rural communities based on five essential keys to prevent foodborne diseases. Methods: The study population (n=90) comprised adult from the Mayan communities of Mexico. Participants were stratified into three groups according to their level of academic education: primary (GES), secondary (GHS), and mixed (GM). A pre-and posttest was designed to incorporate 36 variables: knowledge, 25 attitudes, and 26 habits. An inferential Χ2 analysis was performed to reveal the differences between the pretest and posttest. Results: The intervention registered an advance in knowledge of 13% of the GM, 40% of the GES, and 7% of GHS. Progress was made in attitudes by 79% of GM, 59% of GES, and 80% of GHS. Regarding habits, the association of the term health with behavior was demonstrated, and this was achieved by 82% GM, 66% GES, and 67% GHS. Conclusions: Participants improved their understanding of the personal and psychological factors related to their lifestyle. However, the instrument should be further adapted for groups with varying levels of initial knowledge. New items should be designed and added to emphasize the importance of adopting healthy attitudes and habits.